2022
DOI: 10.3390/fire5040116
|View full text |Cite
|
Sign up to set email alerts
|

The Behaviour of Water-Mists in Hot Air Induced by a Room Fire: Effect of the Initial Size of Droplets

Abstract: This paper presents work on investigating the effect of the initial size of water mist droplets on the evaporation and removal of heat from the fire-induced hot gas layer while travelling through the air in a compartment. The histories of the temperature, diameter and position of droplets with different initial diameters (varied from 100 µm to 1000 µm) are determined considering surrounding air temperatures of 75 °C and 150 °C and a room height of 3.0 m. A water droplet evaporation model (WDEM) developed in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…Field testing is necessary to accurately capture the real behavior of water mist systems in response to a fire event [15]. Previous evaluations of the combined use of water mist and fire suppression mechanisms primarily focused on the general characteristics of the fire plume, such as its geometry, temperature, gas flow speed, and smoke quantity [16][17][18] and found that larger droplets are more effective in penetrating a smoke layer.…”
Section: Introductionmentioning
confidence: 99%
“…Field testing is necessary to accurately capture the real behavior of water mist systems in response to a fire event [15]. Previous evaluations of the combined use of water mist and fire suppression mechanisms primarily focused on the general characteristics of the fire plume, such as its geometry, temperature, gas flow speed, and smoke quantity [16][17][18] and found that larger droplets are more effective in penetrating a smoke layer.…”
Section: Introductionmentioning
confidence: 99%
“…Mitigation of explosions was investigated as an additional action by water mist in highly hazardous storage facilities [12]. Its success can be mainly attributed to a discharge of generally less water than that by sprinkler systems, since fragmentation into tinier droplets yields a faster evaporative action [13,14]. Dedicated studies were also focused on water-mist action in suppressing compartment fires, mainly emphasizing the need for controlled discharge [15] and systems that govern activation on a detection-based feedback [16].…”
Section: Introductionmentioning
confidence: 99%
“…To date, extensive numerical studies have been performed to study the suppression behaviour of water-mist systems under different configurations and fire scenarios. Wang et al [23], Liu et al [24] and Mahmud et al [25] have studied the effects of different droplet sizes offered on droplets' penetrability and the evaporating rate at the flame region. Other spray characteristics such as spray angle [26], nozzle type [27], flow rate and operating pressure [28] have also been investigated through numerical studies.…”
Section: Introductionmentioning
confidence: 99%